PENYULUHAN HUKUM BAHAYA NARKOTIKA DAN PENANGANGANANNYA BAGI GENERASI MUDA GEREJA DI KABUPATEN MERAUKE - Pieter, Salvadoris; Parera, Zegovia (Sagu: Jurnal Pengabdian Masyarakat, 2024)
Narcotics abuse is one of the serious challenges faced by the young generation, including the young generation of churches in Merauke Regency. Its devastating impact not only on individuals, but also families and communities, requires special attention. This service describes the implementation of a legal education program with a focus on the dangers of narcotics and steps to handle them aimed at the young generation of the church in Merauke Regency.  Therefore, the solution offered is to conduct legal education on the dangers of narcotics and how to deal with them for the young generation of the church in Merauke Regency. This will increase knowledge and have great potential in preventing narcotics crimes among young people, especially the younger generation of the church. This activity aims to increase understanding of the law, build awareness of the bad effects of narcotics, and encourage the active role of the younger generation in prevention and rehabilitation. Counseling methods include exposure to legal material based on Law Number 35 of 2009 concerning Narcotics, interactive discussions, and case simulations.  The output of this activity is a journal. This includes providing material and legal rules governing narcotics crimes from resource persons and case studies.  The results of the activity showed an increase in participants' understanding of the dangers of narcotics, related legal mechanisms, and handling strategies. It is hoped that this counseling will become a model of service that can be applied in other areas to empower the younger generation of the church to face the threat of narcotics more effectively.